Profession or passion?: Teaching Chinese in London Chinese complementary schools (UCL Press, 2014)
As academic interest in Chinese complementary schools has grown, insufficient attention has been paid to the role and experiences of teachers working in these schools. This paper has drawn from accounts of Chinese complementary schoolteachers in London, together with the author's personal experiences of working as a teacher in one such school. The paper analyses recent changes in the demographic of these schools and also the changing discourse field that surrounds them. The discussion then progresses to consideration of the impact of these changes upon Chinese complementary schools, especially with regard to teachers' experience. This paper examines the pattern of professional training that exists among this growing segment of teachers, identifying issues for the future. The paper asks why it is that so many teachers who bring very positive commitment and engagement to their professional role do so in the face of poor funding and pay. Finally, the paper focuses on new challenges for teachers in their classrooms with the aim of providing directions for future development and research.